LA DOCENCIA EN LA CARRERA DE CIENCIAS DE LA EDUCACiÓN DE LA UNIVERSIDAD NACIONAL DE ITAPÚA:: UN ACERCAMIENTO A LA CONCEPCiÓN E IDENTIDAD DEL PROFESORADO (Journal on studies and research of academic knowledge, 2008)
In this article the doctoral thesis proposal is exposed whose intention orients to the diagnosis and analysis of the reaches and the implicancias of the educational profession in the National University of Itapúa - UNI, more specifically, in the Faculty of Humanities, Social Sciences and Guaraní Culture.The objective of the investigation looks for to include/understand the models of teaching of the professors of the Faculty of Humanities of the National University of Itapúa in the complex frame of the networks of speeches on quality of the education, of elements of professional identity, conceptions of university teaching and styles of learning's.To know the aspects deep that do to the conceptions of the contents, the education, the learning and the evaluation understood from the own speeches of the professors and from a critical glance with scientific approach, allows to establish the bases which they would make possible the strategic redireccionamiento of the education in the university and to jeopardize affectively to the teaching staff with the intentions of an education made the quality and the pertinence.This study is of qualitative-descriptive type, of phenomenological cut.
Keywords: Educational styles; conceptions of education; conceptions of learning, conceptions of the contents; conceptions of the evaluation; professional identity